Аналог формули Келлі - Сильвестра та ряд Пуанкаре алгебри інваріантів тернарної форми - Бедратюк, Л.П. (Український математичний журнал, 2010)
Найдены явная формула для числа νd(n) линейно независимых однородных инвариантов степени n тернарной формы порядка d и формула для ряда Пуанкаре алгебры инвариантов тернарной формы. An explicit formula is obtained for the number ν d (n) of linearly independent homogeneous invariants of degree n of a ternary form of order d. A formula for the Poincaré series of the algebra of invariants of the ternary form is also deduced.